2017
DOI: 10.1002/ijc.30597
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to pregnancy and birth and the risk of childhood brain tumours: The ESTELLE and ESCALE studies (SFCE, France)

Abstract: Little is known of the causes of childhood brain tumors (CBT). The aims of this study were to investigate whether extremes of birth weight were associated with increased risk of CBT and whether maternal preconceptional folic acid supplementation or breastfeeding reduced the risk. In addition, other maternal characteristics and birth related factors were also investigated. We pooled data from two French national population-based case-control studies with similar designs conducted in 2003-2004 and 2010-2011. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 47 publications
1
37
1
Order By: Relevance
“…The outcome of interest in our analysis was childhood brain tumors, classified according to the ICCC-3 [3]. From the enrolled studies [29][30][31][32][33][34][35][36][37][38], we derived the risk estimate of the highest relative to the lowest folate intake for the analysis.…”
Section: Data Collectionmentioning
confidence: 99%
See 3 more Smart Citations
“…The outcome of interest in our analysis was childhood brain tumors, classified according to the ICCC-3 [3]. From the enrolled studies [29][30][31][32][33][34][35][36][37][38], we derived the risk estimate of the highest relative to the lowest folate intake for the analysis.…”
Section: Data Collectionmentioning
confidence: 99%
“…In our selection, 9 studies reported OR [29][30][31][32][33][34][35][36]38] and one study reported the hazard ratio [37]. For the overall estimation, the hazard ratio was taken as an approximation to the OR, and the meta-analysis was performed as if all types of ratio were ORs.…”
Section: Doi: 101159/000490249mentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have showed that the number of people suffering and dying from brain tumor has increased to 300 per year during the last few decades [34]. Brain tumor is statically the second leading cause of child death [3]. Brain tumor is formed due to the abnormal cell growth in brain tissues.…”
Section: Introductionmentioning
confidence: 99%